The Structure and Stability of High Temperature Intermetallic Phases for Application within Coating Systems - Roberts, Tracey (Cranfield University, 2009)
The reduction of noise and emissions is becoming increasingly important in civil aircraft jet engines as well as requirements for reduced fuel consumption and improved efficiency. This has resulted in the drive towards increasing turbine entry temperatures and the development of thermal barrier coatings (TBCs). Due to the effectiveness of the platinum-modified nickel aluminides currently used as bond coat layers for Ni-based superalloy TBCs, higher temperature ruthenium-containing bond coat layers are being examined as a possible low cost alternative to platinum. Rolls Royce have a patented process, whereby precious metal layers directly react with single crystal substrate alloys to form an aluminium containing surface coating. The aluminium is sourced from the single crystal alloy and the coating so formed has a + structure, but contains other intermetallic phases due to the reaction between the coating and the single crystal substrate. This bond coat layer acts as a diffusion barrier, which limits interdiffusion between the coating and the substrate. The aim of this research was to examine the stability of various phases within platinum and ruthenium-containing multilayer systems formed during the above reaction process and to determine the most stable intermetallics for inclusion in future coating systems. Foil samples were manufactured using multilayer sputter coating methods and the exothermic formation of these phases was examined using differential scanning calorimetry. The identification of the phases formed was carried out using X-ray diffraction. It was found that the interdiffusion between the initial multi-layers had been incomplete during the samples heat treatment, and so more intermetallic phases formed in some samples than aimed for. Hence, from the large number of samples studied it was shown that, as a result of kinetic factors, the reaction onset (or trigger) temperature was not related to the enthalpy of the intermetallic phases formed or the sample compositions within a target phase field. For the β-phase (NiAl) type intermetallic systems, the samples that produced the highest enthalpy values (i.e. the most stable intermetallic compounds) were those with the nominal compositions (in atomic %) of; ‘47Ni53Al’, ‘48Ni6Pt46Al’ and ‘51Ni7Ru42Al’. For the γ΄-phase (Ni3Al) type intermetallic systems, the highest enthalpy values were from samples with nominal compositions of ‘60Ni16Pt24Al’ and ‘74Ni5Ru24Al’